1998
DOI: 10.4096/jssj1995.48.67
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary environments based on textures of surface sediments and sedimentation rates in the South Yatsushiro Kai (Sea), southwest Kyushu, Japan

Abstract: The main purpose of this study is to clarify the relation between characteristics of sediments and environmental conditions, based on the analysis of core samples from the South Yatsushiro Kai (Sea) which is located off the west coast of central Kyushu Island, Japan.Bottom sediment samples were collected at 74 stations in the southern part of the Yatsushiro Kai using gravity corers in March 1996. 62 core samples were used for the mechanical analysis by the settling-tube method, and Q-mode cluster analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
7

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 7 publications
(2 reference statements)
0
9
0
7
Order By: Relevance
“…Other areas occupied by finer grained-sediments which are influenced by weak tidal currents less than 0.3 m/s (Figures 5 and 6). Strong relationship between the distribution of median diameter of bottom surface sediments and currents system was also found in the Dumai Coastal Waters of Rupat Strait which located close to the Mesjid River Estuary and in the strait which connected to the estuary [Rifardi and Syahrul, 2013], and this relationship is also recognized in the South Yatsushiro Sea, southwest Kyushu Japan [Rifardi et al, 1998]. The relationship between particle size and water velocity was also explained by Koiter et al [2013].…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Other areas occupied by finer grained-sediments which are influenced by weak tidal currents less than 0.3 m/s (Figures 5 and 6). Strong relationship between the distribution of median diameter of bottom surface sediments and currents system was also found in the Dumai Coastal Waters of Rupat Strait which located close to the Mesjid River Estuary and in the strait which connected to the estuary [Rifardi and Syahrul, 2013], and this relationship is also recognized in the South Yatsushiro Sea, southwest Kyushu Japan [Rifardi et al, 1998]. The relationship between particle size and water velocity was also explained by Koiter et al [2013].…”
Section: Resultsmentioning
confidence: 91%
“…The samples were used for analysis of mechanical grain size. The gravel and sand proportions were determined by sieving and were weighed oven dried (Rifardi et al,1998). The settling tube method was utilized to determine the mud proportion.…”
Section: The Methodsmentioning
confidence: 99%
“…Based on Rajar et al (2004), contaminated area has reached the Yatsushiro Sea, mostly before, or during the dredging process 7) . Rifardi et al, (1998) also reported based on their field survey result, there were southern and northern sediment transports that contained mercury in Yatsushiro Sea 8) . Recently, Snyder (2012) 9) mentioned that the Asahi Shinbun reported that between January 2005 and June 2010 around 568 people who live in the designated area for relief measures in Amakusa region, the western part of Yatsushiro Sea, plus 160 people who live outside of the designated area have shown similar symptoms with Minamata Disease patients 9) .…”
Section: Introductionmentioning
confidence: 87%
“…(1998) 8) . But here, regardless the mercury concentration, we only consider to the similarity of the pattern and direction of the sediment transport around Minamata Bay and in the Yatsushiro Sea.…”
Section: (3) Boundary Conditions and Model Parametersmentioning
confidence: 99%
See 1 more Smart Citation